Comparison of Temperature-Controlled Dispersive and Hollow Fiber Microextraction Techniques Using Ionic Liquid for Determination of Tributyltin and Triphenyltin in Water - Sheikhloie, Hossein; Saber Tehrani, Mohammad; Waqif Husain, Syed (Asian Journal of Chemistry, 2012)
Two liquid phase microextraction techniques termed ionic liquid based hollow fiber liquid phase microextraction and temperature-controlled ionic liquid dispersive liquid phase microextraction have been compared for the analysis of tributyltin and triphenyltin in environmental water samples by high performance liquid chromatography fluorimetric detection. Experimental conditions have been investigated for both methods. Under the optimal conditions, the limits of detection for tributyltin and triphenyltin obtained by ionic liquid based hollow fiber liquid phase microextraction and temperature-controlled ionic liquid dispersive liquid phase microextraction were ranged from 0.46 to 0.72 μg/L and 0.24 to 0.32 μg/L and the relative standard deviations (RSDs, n = 5) were in the range of 6.8-0.72 % and 2.6-3.1 %, respectively. Both methods were found to be simple, fast, efficient and inexpensive. Compared with ionic liquid based hollow fiber liquid phase microextraction, the advantages of temperature-controlled ionic liquid dispersive liquid phase microextraction technique were less extraction time. Both methods were applied to the analysis of tributyltin and triphenyltin in sea water, waste water and river water.